Architecture as a Medium of Exchange - Michael Rotondi (Oz, 1993)
The notion of universal order is ancient, but when the scientific method came into being four hundred years ago it led to theories that have proved revelatory in their uncovering of the hidden order in the universe - an order governed by a system of natural laws not able to be detected by the senses alone.